Analisis SWOT Pemasalan Olahraga Fullball - Fauzan Zufar Athallah; Hijrin Fitroni; Himawan Wismanadi; Mokhamad Nur Bawono (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Fullball is one of the new sports that has gained a lot of attention from the public. Fullball combines several well-known ball sports such as basketball, futsal and handball. The development of Fullball sports is currently influenced by the marketing of Fullball sports to the public, so the right strategy is needed to introduce Fullball sports. This research was conducted with the objective of conducting a SWOT analysis to see the Strengths, Weaknesses, Opportunities and Threats through the Major League competition as an activity to introduce the new sport of Fullball to the wider community, efficiently, and sustainably. The components analysed include quantitative data through interviews and the author's involvement in Fullball sports. The results showed that the main strengths of Fullball are its uniqueness as a new sport and the strong support from brand sponsors and the government in the implementation of the competition. However, weaknesses include the lack of a solid sports ecosystem, limited facilities and accessibility, and limited resources. In addition, opportunities that can be utilized include the trend of exploring new sports among young people, active use of social media, and the potential for strategic cooperation with various parties. Meanwhile, threats that need to be anticipated are financial instability and low levels of participation from players and audiences. The conclusion of this study emphasizes the importance of strategies that maximize strengths and opportunities, as well as address weaknesses and anticipate threats to support Fullball's marketing success at the national level.